Persepsi Pelaku UMKM Industri Halal terhadap Implementasi Kebijakan Pajak UMKM : Pendekatan Fenomenologi - Iffan Al-Faris; Dicko Syah Purnama Putra; Mashudi Mashudi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This research examines the perceptions of MSME actors regarding the implementation of MSME tax policies in Indonesia, The aim of the research is to explore in depth the perceptions of MSME actors towards tax policy and identify the factors that influence it. The research method used is qualitative phenomenology, with data collection through in-depth interviews with MSME actors. The research results show a diversity of perceptions, ranging from positive views which see policies as supporting business formalization and opening access to financing facilities, to negative views which see them as an additional burden, especially for businesses with thin margins. Factors that influence perceptions include the level of tax knowledge, business experience, characteristics of the business sector, access to information, and the ability to utilize technology. The research conclusions emphasize the need for a more nuanced and adaptive approach in the formulation and implementation of MSME tax policy. The government needs to consider the diverse characteristics and needs of the MSME sector, increase tax education and outreach, and improve the accessibility of tax information and services. Continuous dialogue between policy makers and MSME actors is needed to develop an effective tax system in increasing state revenues and supporting the growth of the MSME sector.